2022
DOI: 10.3390/foods11030442
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Use of Different Temperature and Calcium Chloride Treatments during Storage on the Quality of Fresh-Cut “Xuebai” Cauliflowers

Abstract: This study revealed the effect of the use of different temperature and calcium chloride (CaCl2) treatments on the storage quality of fresh-cut “Xuebai” cauliflowers. Fresh-cut “Xuebai” cauliflowers were soaked with 2% CaCl2 solution at different temperatures. The change in the firmness, color, and ascorbic acid (ASA), total glucosinolates (TGLS), polygalacturonase (PG), and lipoxygenase (LOX) content of fresh-cut “Xuebai” cauliflowers during the cold storage period was assessed. In addition, the sensory qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In another study, the L* value of cauliflower decreased during 28 days of storage at 0±1°C, while the b* value increased (Dhall et al, 2010). Mu et al (2022) reported that the L* value of fresh-cut cauliflower decreased during storage (15 days at 4 °C), while a* and b* values increased. Researchers also found that the L* value decreased compared to before storage, while the a* and b* values increased.…”
Section: Changes In Color Propertiesmentioning
confidence: 91%
“…In another study, the L* value of cauliflower decreased during 28 days of storage at 0±1°C, while the b* value increased (Dhall et al, 2010). Mu et al (2022) reported that the L* value of fresh-cut cauliflower decreased during storage (15 days at 4 °C), while a* and b* values increased. Researchers also found that the L* value decreased compared to before storage, while the a* and b* values increased.…”
Section: Changes In Color Propertiesmentioning
confidence: 91%
“…Green tea and rosemary ethanolic extracts function as antifungals in these pads. These pads inhibit fungal development, maintain quality, and extend raspberry fruit shelf life by 14 days [82].…”
Section: Coldmentioning
confidence: 99%
“…Several studies have tested dipping treatments with calcium (Ca) salts to extend the shelf-life of products. Ca enrichment, in fact, has several advantages, including the reduction of microbial growth due to a decrease in activity water, the improvement of texture, acceptability, and storability, and the prevention of browning due to the oxidation phenomena and the development of off-flavors in fresh-cut foods [ 80 , 81 , 82 , 83 ]. Giacalone and Chiabrando [ 84 ] compared the effect of dipping in Ca salts (chloride or propionate) and citric acid solutions on apple cubes, highlighting an improvement in firmness, color, sensory attributes, and browning inhibition on fruits treated with Ca chloride and citric acid.…”
Section: Postharvest Strategies To Extend the Shelf-life Of Fruit And...mentioning
confidence: 99%